Analisis Determinan Tabungan di Indonesia: Suatu Aplikasi Teori Life Cycle Hypothesis - Stesia Selumiel Sangka; Birgitta Dian Saraswati (Universitas Kristen Wira Wacana Sumba, 2025)
The role of savings in an economy is very important, an increase in savings will increase investment and economic growth. This study aims to determine how per capita income, the number of productive age population, and interest rates affect savings in Indonesia using the Life Cycle Hypothesis (LCH) theoretical framework. Using the Partial Adjustment Model (PAM) analysis technique with an observation period of 1991-2023, this study provides results that the per capita income variable is proven to have a positive and significant effect, as well as the interest rate variable is proven to have a negative and significant effect. While the variable number of productive age population is proven to have no effect. This indicates that the Life Cycle Hypothesis (LCH) theory has not been proven to apply in Indonesia. This is thought to be due to the high age dependency ratio in Indonesia. The policy implications of the findings in this study are in an effort to encourage national savings in addition to policies that increase per capita income, also with policies that can reduce the age dependency ratio for example by optimizing the old age security program by requiring all companies to include their employees in the old age security program. In addition, the finding that interest rates have a negative effect on savings, which is thought to be a response to rising inflation, means that the inflation targeting monetary policy currently implemented by Bank Indonesia is the right policy in an effort to encourage national savings